Agrifood systems policy research: agricultural growth, hunger, and poverty. Historical evolution of agrifood systems in Pakistan - Gazdar, H. (International Water Management Institute (IWMI). CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2023)
This study probes assumptions which underpin current thinking about the transformation of Pakistan’s agrifood systems by identifying and examining key turning points from the 1840s onwards in sub-regions of the Indus irrigated plains. It highlights historical antecedents of contemporary agrifood systems including: the political-strategic goals of colonial reformers, origins of inter-regional disparities, the elevation and marginalisation of various social groups and agrarian classes, ambivalence towards markets and market-players, and the entrenched political economy of land and water resources.